Optimasi Electromagnetic Regenerative Shock Absorber (ERSA) Tipe Magnet Batang Alnico pada Suspensi Belakang Multi Purpose Vehicle (MPV) - Andri Fadhil; Hasan Maksum; Wanda Afnison (AEEJ : Journal of Automotive Engineering and Vocational Education, 2020)
This study aims to optimize the electrical energy generation generated by the Electromagnetic Regenerative Shock Absorber (ERSA) type of alnico bar magnet on the rear suspension Multi Purpose Vehicle. This study uses the Taguchi Experiment method by varying the number of copper windings (1000, 1500, 2000 turns), wire diameter (0.2 mm, 0.3 mm, 0.4 mm) and large air gap (2 mm, 3 mm, 4 mm). The results showed the highest electrical voltage generation of 1.68V in 2000 wire coil variants, 0.4 mm wire diameter and 4 mm air gap. while the lowest voltage generated electricity is 0.9V on 1000 wire coil variants, 0,2 mm diameter diameter and 2 mm air gap. That is, an increase in the voltage generated by using the Taguchi Experiment method from previous studies which produced a voltage of 121-131mV. Penelitian ini bertujuan untuk mengoptimalkan energi listrik bangkitan yang dihasilkan oleh Elektromagnetik Regenerstif Shok Absorber (ERSA) tipe magnet batang alnico pada suspensi belakang Multi Purpose Vehicle. Penelitian ini menggunakan metode Eksperimen Taguchi dengan memvariasikan jumlah lilitan tembaga (1000, 1500, 2000 lilitaan), diameter kawat (0,2 mm, 0,3 mm, 0,4 mm) dan besar celah udara (2 mm, 3 mm, 4 mm). Hasil penelitian didapatkan tegangan listrik bangkitan paling tinggi sebesar 1,68V pada varian lilitan kawat 2000, diameter kawat 0,4 mm dan celah udara 4 mm. sedangkan tegangan listrik bangkitan paling rendah sebesar 0,9V pada varian lilitan kawat 1000, diameter kawar 0,2 mm, dan celah udara 2 mm. Artinya, terjadi peningkatan tegangan yang dihasilkan dengan menggunakan metode Eksperimen Taguchi dari penelitian sebelumnya yang menghasilkan tegangan sebesar 121-131mV.